2021
DOI: 10.1002/suco.202000707
|View full text |Cite
|
Sign up to set email alerts
|

Study on nonlinear damping behavior of damaged recycled aggregate concrete beams

Abstract: An experimental study on the nonlinear damping behavior of recycled aggregate concrete (RAC) beams is conducted through subjecting dynamic loadings at the different damage stages. The effects of the loading frequency, loading amplitude, damage, recycled aggregate, and replacement percentage on the energy dissipation by damping and the equivalent viscous damping ratio (EVDR) of the RAC beams are analyzed. The experimental results show that the energy dissipation and the EVDR are not directly influenced by the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Therefore, the reclamation technology of concrete waste has been developed, where concrete waste is commonly crushed into recycled aggregate and reutilized in newmade concrete 5 . Because of the inferior properties of recycled aggregate relative to natural aggregate, substituting recycled aggregate for natural aggregate in concrete is detrimental to the drying shrinkage, 6,7 long‐term durability performance, 8,9 and mechanical properties 10–12 . Although the application of nanoparticle incorporation, carbonation modification, physical and chemical enhancement contributes to improve the properties of recycled aggregate, the improvement efficiency and economic benefits are not satisfactory for large‐scale production of recycled aggregate with high quality 13–15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the reclamation technology of concrete waste has been developed, where concrete waste is commonly crushed into recycled aggregate and reutilized in newmade concrete 5 . Because of the inferior properties of recycled aggregate relative to natural aggregate, substituting recycled aggregate for natural aggregate in concrete is detrimental to the drying shrinkage, 6,7 long‐term durability performance, 8,9 and mechanical properties 10–12 . Although the application of nanoparticle incorporation, carbonation modification, physical and chemical enhancement contributes to improve the properties of recycled aggregate, the improvement efficiency and economic benefits are not satisfactory for large‐scale production of recycled aggregate with high quality 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Because of the inferior properties of recycled aggregate relative to natural aggregate, substituting recycled aggregate for natural aggregate in concrete is detrimental to the drying shrinkage, 6,7 long-term durability performance, 8,9 and mechanical properties. [10][11][12] Although the application of nanoparticle incorporation, carbonation modification, physical and chemical enhancement contributes to improve the properties of recycled aggregate, the improvement efficiency and economic benefits are not satisfactory for large-scale production of recycled aggregate with high quality. [13][14][15] Therefore, researchers around the world put forward a new technology method of reclaiming construction and demolition waste into active recycled powder (RP) as an alternative binder or supplementary cementitious material (SCM), and the utilized RP (<0.15 mm) in new cement-based materials reduces the dosage of cement, which is cost-effective and eco-friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the maximum deflection response will be overestimated. Moreover, it is still a controversial issue regarding how to model the damping mechanism for a sudden column removal scenario [19,47,48], e.g., viscous damping or Coulomb damping [23]. For instance, the studies have identified drawbacks associated with the use of Rayleigh damping based on initial stiffness, in which the initial stiffness may introduce in the unwanted artificial viscous forces [14,49].…”
mentioning
confidence: 99%